Global Reprogramming of Gene Transcription in Trichoderma reesei by Overexpressing an Artificial Transcription Factor for Improved Cellulase Production and Identification of Ypr1 as an Associated Regulator - Zhang, Fei; Li, Jia-Xiang; Champreda, Verawat; Liu, Chen-Guang; Bai, Feng-Wu; Zhao, Xin-Qing (Frontiers in Bioengineering and Biotechnology, 2020)
Synthetic biology studies on filamentous fungi are providing unprecedented opportunities for optimizing this important category of microbial cell factory. Artificial transcription factor can be designed and used to offer novel modes of regulation on gene transcription network. Trichoderma reesei is commonly used for cellulase production. In our previous studies, a plasmid library harboring genes encoding artificial zinc finger proteins (AZFPs) was constructed for engineering T. reesei, and the mutant strains with improved cellulase production were selected. However, the underlying mechanism by which AZFP function remain unclear. In this study, a T. reesei Rut-C30 mutant strain T. reesei U5 bearing an AZFP named as AZFP-U5 was focused, which secretes high level protein and shows significantly improved cellulase and xylanase production comparing with its parental strain. In addition, enhanced sugar release was achieved from lignocellulosic biomass using the crude cellulase from T. reesei U5. Comparative transcriptome analysis was further performed, which showed reprogramming of global gene transcription and elevated transcription of genes encoding glycoside hydrolases by overexpressing AZFP-U5. Furthermore, 15 candidate regulatory genes which showed remarkable higher transcription levels by AZFP-U5 insertion were overexpressed in T. reesei Rut-C30 to examine their effects on cellulase biosynthesis. Among these genes, TrC30_93861 (ypr1) and TrC30_74374 showed stimulating effects on filter paper activity (FPase), but deletion of these two genes did not affect cellulase activity. In addition, increased yellow pigment production in T. reesei Rut-C30 by overexpression of gene ypr1 was observed, and changes of cellulase gene transcription were revealed in the ypr1 deletion mutant, suggesting possible interaction between pigment production and cellulase gene transcription. The results in this study revealed novel aspects in regulation of cellulase gene expression by the artificial regulators. In addition, the candidate genes and processes identified in the transcriptome data can be further explored for synthetic biology design and metabolic engineering of T. reesei to enhance cellulase production.